Kajian Jenis Burung-Burung yang Dipelihara oleh Penghobi dan Tingkat Perdagangannya di Kota Kupang (Studi Kasus di Kecamatan Oebobo dan Kecamatan Kelapa Lima) - Alimus Adrianus Tri Putra; Mari M. E. Purnama; Oki Hidayat; Fadlan Pramatana (Wana Lestari, 2025)
The phenomenon of bird keeping and trading has become an integral part of community life, especially in urban areas, leading to a dynamic interplay between hobbies, economy, and conservation issues. This qualitative descriptive research aims to examine the types of birds kept by hobbyists and their trade levels, as well as to identify the conservation status of birds found in Oebobo and Kelapa Lima Districts, Kupang City. The study involved 15 informants selected through purposive sampling via observation, interviews, and documentation. The research results show that hobbyists keep 10 bird species: Murai Batu, Kenari, Cucak Ijo, Lovebird, Parkit, Kacer, Perkutut, Tekukur, Finch, and Anis Cendana. The majority of hobbyists (86.67%) have 5-10 years of experience with intensive collections (5-15 birds), dominated by Lovebird, Kenari, and Murai Batu. The primary motivations for hobbyists are personal enjoyment, leisure activities, and business opportunities, supported by active communities. The main problems faced by hobbyists include sick/stressed birds and birds that do not sing ("gacor"), which are addressed by maintaining cage cleanliness, consulting with experts, and providing vitamins. Bird purchases are predominantly from friends or markets, and basic care is generally good, but knowledge of disease prevention needs improvement. In terms of trade, buying and selling activities are common, although only a small proportion (6 out of 15) are primary traders. Traders' motivations include potential profit and a love for birds, with good prospects and an upward price trend. The main problems for traders are marketing/sales, sourcing chicks, and bird care, which are overcome by establishing supplier relationships and social media promotion. Sales are predominantly local through kiosks/bird markets, with growing online sales. Conservation implications indicate that out of the 10 species, 70% are listed as Least Concern, 20% as Near Threatened (Anis Cendana, Lovebird), and 10% as Endangered (Cucak Ijo). Cucak Ijo is protected under Ministry of Environment and Forestry Regulation No. 106 of 2018, while Murai Batu and Lovebird are listed in CITES Appendix II. The low level of regulation dissemination and compliance with permitting potentially threatens endangered species. Therefore, the dynamic bird market in Kupang requires stronger education, socialization, and law enforcement to ensure responsible and sustainable practices in accordance with conservation regulations.